PENGARUH VARIASI VOLUME LIMBAH SERBUK KAYU MAHONI TERHADAP KEKUATAN FISIK, MEKANIK DAN MIKROSTRUKTUR KOMPOSIT PARTIKEL - Desiasni, Rita; Widyawati, Fauzi; Nabila, Maitsa Fikri; Saiful, Muhammad (Hexagon Jurnal Teknik dan Sains, 2024)
The strength of the mechanical and physical properties of particle composite materials is influenced by the volume fraction of the powder and matrix. The pretreatment was carried out by soaking 2% NaOH for 1 hour. The results of the MOE treatment mechanical highest test value at the powder volume fraction of 30:70%, which was 6145.51 kgf/cm² and the highest MOR test value at the 30:70% volume fraction, which was 167.38 kgf/cm². Meanwhile, the highest non-treatment MOE value at the 30:70% powder volume fraction was 5540.9 kgf/cm² and the highest MOR test value at the 30:70% volume fraction was 156.6 kgf/cm². The results of the physical properties test were the highest density at the 30:70% powder volume fraction of 0.87 gr/cm³ and the highest density at the 30:70% non-treatment powder volume fraction of 0.78 gr/cm³. The results of the MOE mechanical test do not meet the JIS A 5908-2003 standard while the MOR mechanical test and physical test have met the JIS A 5908- 2003 standard. The results of microstructure testing showed that at a fraction of powder volume of 30:70% it was seen that the particles were coarser which blended perfectly with the matrix.